Late Pleistocene and Holocene chitons (Mollusca, Polyplacophora) from Uruguay: Palaeobiogeography and palaeoenvironmental reconstruction in mid latitudes of the southwestern Atlantic - Rojas, A. (2011)
Here we present a revision of the fossil record of chitons (Mollusca, Polyplacophora) of Late Pleistocene and Holocene marine deposits of Uruguay and discuss their potential for palaeoenvironmental reconstruction. Chitons were recorded as isolated valves in bivalve- and gastropod-rich assemblages. They are represented by the species Chaetopleura angulata (Spengler), C. isabellei (d'Orbigny), C. asperrima (Gould) and Ischnochiton striolatus (Gray). The last two species are recorded for the first time as fossils not only in Uruguay but also in South America. Exclusively recorded for the Late Pleistocene is the warm water species I. striolatus, whose current southern range limit is located in Santa Catarina, Brazil. Higher temperatures than at present are inferred for the Uruguayan coast during the Late Pleistocene, probably driven by the southward influence of the warm Brazilian Current along the eastern margin of South America. Chitons from Holocene deposits show a wider geographic distribution along the Uruguayan coast in comparison to current distributions. They are recorded where an estuarine and eurihaline fauna lives today, which suggests the former existence of marine conditions. This is explained by the westward displacement of the marine front in the Uruguayan coast during the Holocene transgressive events. Chitons have proven to be useful palaeoenvironmental proxies for the reconstruction of salinity and temperature trends in the Uruguayan coast during the climatic oscillations of the Late Pleistocene and Holocene epochs. As such, their patterns of distribution are related to the recent physical evolution of the Southwestern Atlantic Ocean.